2020
DOI: 10.1186/s12935-020-01625-w
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T-cell immune stimulation of HER2 + breast cancer cells alters response to trastuzumab in vitro

Abstract: Introduction The HER2 + tumor immune microenvironment is composed of macrophages, natural killer cells, and tumor infiltrating lymphocytes, which produce pro-inflammatory cytokines. Determining the effect of T-cells on HER2 + cancer cells during therapy could guide immunogenic therapies that trigger antibody-dependent cellular cytotoxicity. This study utilized longitudinal in vitro time-resolved microscopy to measure T-cell influence on trastuzumab in HER2 + breast cancer. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Previously collected data revealed that trastuzumab has the potential to reprogram the immunosuppressive components of the tumor microenvironment and could contribute to anti-tumor responses. The evaluation of immune cell characterization and impact on tumor regression in this treatment regimen is needed to further elucidate the mechanisms contributing to enhanced tumor regression in the combination treatment group [ 29 ]. Although no significant differences were shown in hypoxia and the vascular maturation index, previous studies using longitudinal imaging have revealed that trastuzumab can reduce hypoxia and increase vascular perfusion [ 17 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously collected data revealed that trastuzumab has the potential to reprogram the immunosuppressive components of the tumor microenvironment and could contribute to anti-tumor responses. The evaluation of immune cell characterization and impact on tumor regression in this treatment regimen is needed to further elucidate the mechanisms contributing to enhanced tumor regression in the combination treatment group [ 29 ]. Although no significant differences were shown in hypoxia and the vascular maturation index, previous studies using longitudinal imaging have revealed that trastuzumab can reduce hypoxia and increase vascular perfusion [ 17 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…For in vitro live cell imaging experiments, SCC1, FADU and OSC19 cell lines were transfected to express green fluorescent protein (GFP) for longitudinal tracking of cell viability. The plasmid and protocol used to induce stable nuclear transfection were previously described 27 . Briefly, cell lines were co-transfected with pCMV (CAT) T7-SB100 (Addgene plasmid #34879) and a GFP clone Sleeping Beauty compatible vector (Addgene plasmid #60525).…”
Section: Methodsmentioning
confidence: 99%
“…Addressing the immunosuppressive mechanisms associated with HER2 signaling can help overcome resistance to HER2-targeted therapies and immunotherapies. The rationale is that HER2-targeted therapies can enhance antigen presentation and T-cell activation, making tumors more susceptible to checkpoint blockade [72]. The interplay between HER2 signaling and immune regulation is complex and has significant implications for developing and optimizing cancer therapies.…”
Section: Her2 and Immune Regulationmentioning
confidence: 99%